Haemocompatibility of iron oxide nanoparticles synthesized for theranostic applications: a high-sensitivity microfluidic tool - Rodrigues, Raquel Oliveira (2016)
The poor heating efficiency of the most reported magnetic nanoparticles (MNPs), allied to the lack of comprehensive biocompatibility and haemodynamic studies, hampers the spread of multifunctional nanoparticles as the next generation of therapeutic bio-agents in medicine. The present work reports the synthesis and characterization, with special focus on biological/toxicological compatibility, of superparamagnetic nanoparticles with diameter around 18 nm, suitable for theranostic applications (i.e. simultaneous diagnosis and therapy of cancer). Envisioning more insights into the complex nanoparticle-red blood cells (RBCs) membrane interaction, the deformability of the human RBCs in contact with magnetic nanoparticles (MNPs) was assessed for the first time with a microfluidic extensional approach, and used as an indicator of haematological disorders in comparison with a conventional haematological test, i.e. the haemolysis analysis. Microfluidic results highlight the potential of this microfluidic tool over traditional haemolysis analysis, by detecting small increments in the rigidity of the blood cells, when traditional haemotoxicology analysis showed no significant alteration (haemolysis rates lower than 2 %). The detected rigidity has been predicted to be due to the wrapping of small MNPs by the bilayer membrane of the RBCs, which is directly related to MNPs size, shape and composition. The proposed microfluidic tool adds a new dimension into the field of nanomedicine, allowing to be applied as a highsensitivity technique capable of bringing a better understanding of the biological impact of nanoparticles developed for clinical applications.